If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 13 = 2y + 22 Reorder the terms: 13 + 5y = 2y + 22 Reorder the terms: 13 + 5y = 22 + 2y Solving 13 + 5y = 22 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 13 + 5y + -2y = 22 + 2y + -2y Combine like terms: 5y + -2y = 3y 13 + 3y = 22 + 2y + -2y Combine like terms: 2y + -2y = 0 13 + 3y = 22 + 0 13 + 3y = 22 Add '-13' to each side of the equation. 13 + -13 + 3y = 22 + -13 Combine like terms: 13 + -13 = 0 0 + 3y = 22 + -13 3y = 22 + -13 Combine like terms: 22 + -13 = 9 3y = 9 Divide each side by '3'. y = 3 Simplifying y = 3
| 6x-4-4x=2x-4 | | 4x+15=24 | | 24-64n=-8(-3+8n) | | 7x-13=42 | | 4x^2-17x-15=30 | | -85=5(2n-3) | | 3x+10=2x-x+18 | | 11x+25=78 | | -2(z-3)-4=18 | | -2-(12x+8)+17=3+x-(13x-4) | | -12z-29=5(z+6)-195 | | 5(v-8)-2=5v+29 | | a(t)=t^2-6t+24 | | 1.6+0.2x=0.4x-3.2 | | 60x^2+300x=0 | | 12+v=-9 | | 12x-18=53 | | (3x-x)(x+3.464)=0 | | 6m-19=-2(-3m+8) | | 3x+27=102 | | 12(4-6x)+8=5 | | k+12=-9 | | 13x-4=17x+4 | | 3a^2-27a^2b=0 | | 25=y+19 | | 18-(9-5x)x=4 | | 3(y+4)=33 | | 678=789 | | 4-2b=-8(4b+7) | | -2(x-5)+3=25 | | 13/8=p-5/2 | | -5x^2-3=77 |